2021
DOI: 10.1371/journal.pone.0248575
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and determinants of drug-related problems among patients admitted to medical wards of southwestern Ethiopian hospitals: A multicenter prospective observational study

Abstract: Background Drug-related problem (DRP) is an event involving drugs that can impact the patient’s desired goal of therapy. In hospitalized patients, DRPs happen during the whole process of drug use such as during prescription, dispensing, administration, and follow-up of their treatment. Unrecognized and unresolved DRPs lead to significant drug-related morbidity and mortality. Several studies conducted in different hospitals and countries showed a high incidence of DRPs among hospitalized patients. Despite the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
(29 reference statements)
4
10
0
Order By: Relevance
“…Patients with one or more medical conditions increased their risk of developing DRPs by 1.48 times when compared to those who did not have any comorbid conditions; this conclusion is consistent with research from the Netherlands [38], India [39], and Norway [40], but differs from a study 8 BioMed Research International conducted in Gondar hospital [41] and a multicenter study in southwestern Ethiopian hospitals [42], which is not statistically different. In fact, as comorbidities and the number of medications rise, patients are at a higher risk of getting DRPs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Patients with one or more medical conditions increased their risk of developing DRPs by 1.48 times when compared to those who did not have any comorbid conditions; this conclusion is consistent with research from the Netherlands [38], India [39], and Norway [40], but differs from a study 8 BioMed Research International conducted in Gondar hospital [41] and a multicenter study in southwestern Ethiopian hospitals [42], which is not statistically different. In fact, as comorbidities and the number of medications rise, patients are at a higher risk of getting DRPs.…”
Section: Discussionsupporting
confidence: 86%
“…Patients who stayed in the hospital for seven or more days were 2.3 times more likely to have DRPs; it is supported by a meta-analysis conducted in Ethiopia [ 45 ], a study in China [ 29 ], and a multicenter prospective study in southwestern Ethiopia [ 42 ]. The reason might be the likelihood of infection in patients who stayed in the hospital for a long time necessitates more management, which raises the expense of patient healthcare.…”
Section: Discussionmentioning
confidence: 92%
“… 21 A multicenter prospective observational study done in Ethiopia among medical ward patients also showed a higher prevalence (67.7%) of DRPs among study participants. 45 The difference might be attributed to the existing practice variation, healthcare professionals’ teamwork level, and availability of medication in the settings.…”
Section: Discussionmentioning
confidence: 99%
“… 44 In a multicenter prospective observational study conducted in Ethiopia, polypharmacy was also reported as a predictor of DRPs. 45 Co-morbidities are associated with DRPs as individuals diagnosed with many clinical conditions will take many drugs that ultimately interact with one another. In a study conducted at Kenyatta National Hospital, advanced stage cervical cancer was also reported to be a predictor of DRPs.…”
Section: Discussionmentioning
confidence: 99%
“…13 Poly-pharmacy: The daily consumption of 5 or more medications. 16 Co-morbidity: Patients diagnosed with two or more diseases. 16…”
Section: Operational Definitionsmentioning
confidence: 99%